2014
DOI: 10.3892/ijo.2014.2538
|View full text |Cite
|
Sign up to set email alerts
|

Deficient HER3 expression in poorly-differentiated colorectal cancer cells enhances gefitinib sensitivity

Abstract: Abstract. Poorly-differentiated colorectal cancers (PD-CRC)show high metastatic potential and poor prognosis. However, molecular characteristics of PD-CRC remain unknown to date, particularly in molecular targeting therapy for patients with PD-CRC. In this study, we examined the expression of EGFR, HER2 and HER3 in PD-CRC by immunohistochemical analysis of archived clinical specimens of primary tumors and investigated the sensitivity of PD-CRC cell lines to gefitinib, a tyrosine kinase inhibitor for EGFR in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…This might be applicable for CRC, also a solid tumor dependent on the HER axis [23]. Nakata et al suggests that HER3 deficiency, EGFR/ HER2 proficiency and poor differentiation enhance the gefitinib effect in CRC cells [24]. Gala et al shows that when resistance to chemotherapy (5-FU + irinotecan) occurs, a patient with HER3 expression in breast cancer can benefit from cetuximab treatment [25].…”
Section: Discussionmentioning
confidence: 99%
“…This might be applicable for CRC, also a solid tumor dependent on the HER axis [23]. Nakata et al suggests that HER3 deficiency, EGFR/ HER2 proficiency and poor differentiation enhance the gefitinib effect in CRC cells [24]. Gala et al shows that when resistance to chemotherapy (5-FU + irinotecan) occurs, a patient with HER3 expression in breast cancer can benefit from cetuximab treatment [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, researchers have found that a heregulin–EGFR–HER3 autocrine signaling axis mediated acquired lapatinib resistance in HER2 + breast cancer models which no longer depended on HER2–HER3–PI3K signal pathway 20 . What׳s more, overexpression of HER3 in COLM-5 cells can lead to significant resistance to gefitinib in vitro and in vivo 21 . All of these studies highlight the central role of HER3 in cancers.…”
Section: The Aberrated Activation Of the Bypass Pathways Induce Resismentioning
confidence: 99%
“…Jacobsen et al [ 31 ] and Li et al [ 32 ] have found that the expression of Her3 increased in breast cancer resistant cell lines (MDA-MB-175-VII) and ovarian cancer drug-resistant cell lines (SKOV3-T) after trastuzumab treatment. Nakata et al [ 33 ] reported that increased Her3 expression increased gefitinib resistance in patients with poorly differentiated CRC. Data from patients with KRAS wild-type mCRC in the GALGB/SWOG 80405 clinical trials revealed that patients with the primary tumor site of mCRC in the left colon could benefit from cetuximab.…”
Section: Discussionmentioning
confidence: 99%